Sejarah Peradaban Islam : Perkembangan Ilmu Pengetahuan pada Masa Pemerintahan Diinasti Bani Abbasiyah - Ainur Riska Amalia (Rihlah: Jurnal Sejarah dan Kebudayaan, 2022)
ABSTRACTThe Abbasid were one of the islamic chalips after the fall of the Ummayad. During the reign of the Abbasiyah, islam experienced very rapid development, so it was the golden age of islam. This article aims to find out the history of the Abbasid, development of science and the decline of the Abbasid. This is a library research with a literature review in the form of jurnals and books. Researchers only use library sources by doing reading activities, record and process research materials. The result of this research is that the Abbasid were founded around the year 132-556H/ 750-1258M. The Abbasid rule was divided into four phases. Science developed rapidly during the Abbasid period. Science is divided into two, naqli and aqli.Keywords: Abbasid, Glory, Science.